2019
DOI: 10.1002/acm2.12699
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of 4D MRI in the delineation of gross and internal tumor volumes in comparison with 4DCT

Abstract: Purpose To evaluate clinical utility of respiratory‐correlated (RC) four‐dimensional magnetic resonance imaging (4DMRI) for lung tumor delineation and motion assessment, in comparison with the current clinical standard of 4D computed tomography (4DCT). Methods and Materials A prospective T2‐weighted (T2w) RC‐4DMRI technique was applied to acquire coronal 4DMRI images for 14 lung cancer patients (16 lesions) during free breathing (FB) under an IRB‐approved protocol, together with a breath‐hold (BH) T1w 3DMRI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 36 publications
(47 reference statements)
5
25
0
Order By: Relevance
“…102,212 Multiple studies have demonstrated the advantage of using extended cine MRI to identify greater variability in target motion ranges, thereby better informing the delineation of the ITV to incorporate these variations, as compared to 4D-CT imaging alone. 96,204,213,214 MIP-based ITVs from 4D-MRI were demonstrated to be feasible and comparable to those typically generated from 4D-CT. 215 In order to further validate the feasibility of using 4D-MRI for ITV delineation, Zhang et al 216 did a comparison study involving 6 radiation oncologists contouring on four different lung cancer patients with a total of 16 lesions of various sizes and at different (central vs. peripheral) locations on T2 4D-MRI, T1 BH MRI, and 4D-CT scans. The physicians contoured gross tumor volumes (GTVs) and the ITV was taken as the composite of the GTVs, without any additional margin.…”
Section: B Investigated Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…102,212 Multiple studies have demonstrated the advantage of using extended cine MRI to identify greater variability in target motion ranges, thereby better informing the delineation of the ITV to incorporate these variations, as compared to 4D-CT imaging alone. 96,204,213,214 MIP-based ITVs from 4D-MRI were demonstrated to be feasible and comparable to those typically generated from 4D-CT. 215 In order to further validate the feasibility of using 4D-MRI for ITV delineation, Zhang et al 216 did a comparison study involving 6 radiation oncologists contouring on four different lung cancer patients with a total of 16 lesions of various sizes and at different (central vs. peripheral) locations on T2 4D-MRI, T1 BH MRI, and 4D-CT scans. The physicians contoured gross tumor volumes (GTVs) and the ITV was taken as the composite of the GTVs, without any additional margin.…”
Section: B Investigated Solutionsmentioning
confidence: 99%
“…In order to further validate the feasibility of using 4D‐MRI for ITV delineation, Zhang et al 216 did a comparison study involving 6 radiation oncologists contouring on four different lung cancer patients with a total of 16 lesions of various sizes and at different (central vs. peripheral) locations on T2 4D‐MRI, T1 BH MRI, and 4D‐CT scans. The physicians contoured gross tumor volumes (GTVs) and the ITV was taken as the composite of the GTVs, without any additional margin.…”
Section: Determining the Internal Target Volume (Itv)mentioning
confidence: 99%
“…4DCT technique presents some shortcomings when compared to other methods like FI 12 or 4DMRI. [13][14][15] For example, 4DCT cannot detect inter-and intrafractional variations in the breathing pattern, which produces an insufficient representation of tumor movement. In addition, its high cost makes few departments have installed this type of equipment and its implementation is still limited even in developed countries.…”
mentioning
confidence: 99%
“…So far, the image resolution is approaching or exceeding that of 4DCT, while the binning artifacts have been substantially reduced or virtually eliminated and scanning time has become clinically acceptable. With the advantages of soft-tissue contrast enhancement and elimination of ionizing radiation, RC-4DMRI technique has been increasingly tested in the clinic and have the potential to play a role in clinical applications (10, 11, 28, 29). However, RC-4DMRI shares the same limitation of one breathing cycle as 4DCT, while using a snapshot of patient respiration as the average motion has been questioned for its validity and reliability (3032).…”
Section: Respiratory-correlated (Rc) 4dmrimentioning
confidence: 99%
“…The DIR-propagated contours were found as good as human contours owing to the high soft-tissue contrasts in T2w 4DMRI. Zhang et al also reported lung tumor delineation in 10 patients from 6 radiation oncologists and compared the results with those from 4DCT and T1w breath-hold images (29). All images were acquired on the simulation day within 2 h. It was found that T2w RC-4DMRI produced a similar GTV to 4DCT but with a much smaller variation among physicians, while T1w MRI based GTV is about 25% smaller.…”
Section: Clinical Evaluations and Applications Of Rc- And Tr-4dmrimentioning
confidence: 99%